Case Report: Diagnostic pitfalls in soft tissue tumors: synovial sarcoma masquerading as venous malformation - Jiang, Xuan; Hu, Li; Chen, Hui; Yang, Xi; Lin, Xiaoxi (Frontiers in Oncology, 2025)
IntroductionSynovial sarcoma (SS) is one of the most prevalent malignant soft tissue sarcomas in children and adolescents. Pediatric populations often present with atypical features, complicating the differentiation from benign intramuscular venous malformations (VMs).​​Case presentationAn 11-year-old male with a four-year history of progressive right plantar pain and a compressible intramuscular mass. The initial magnetic resonance imaging (MRI) findings suggest VM, due to high signal in T2-weighted images. Sclerotherapy under digital subtraction angiography (DSA) revealed unexpected hyper-vascularity, prompting surgical exploration. Histopathology demonstrated spindle and epithelioid cells with hemangiopericytoma-like morphology and mitotic activity, while SS18-SSX1 gene rearrangement confirmed SS. Chemotherapy was then administered, without recurrence over two years.​​ConclusionSS may clinically and radiographically mimic benign vascular anomalies, particularly in children. Discrepancies in vascular dynamics on DSA and atypical imaging features warrant suspicion for malignancy. Early histopathological validation is critical to prevent diagnostic delays, optimize multimodal therapy, and improve outcomes in this aggressive tumor.